Complex Wound Management: Nursing Intervention Protocols-An Updated Review - Al-Mutairi, Hatem Hamijan; Al-Mansour, Hussam Saad; Al-Mutairi, Mohammed Saleh; Al-Muraibid, Najla; Al-Dajani, Naif Nashi; Al-Otaibi, Sultana Mutab; Al-Otaibi, Shujaan Shawan; Al Shamri, Ahlam Matrouk; Aldhafeeri, Mater Mazi Munahi; Alobaida , Haifa Abdulaziz Ali; Almalky , Aydah Nami Joman; Almuteri, Noura Al Homedi; et al. (Journal of Ecohumanism, 2024)
Background: Chronic or complex wounds present a significant healthcare challenge due to their multifactorial etiology and the complex nature of their healing process. These wounds often fail to heal with standard treatments, causing prolonged suffering for patients and considerable healthcare costs. This review discusses nursing intervention protocols for the management of complex wounds, emphasizing both local and systemic factors that influence wound healing. The need for a multidisciplinary approach is evident in improving outcomes for patients with complex wounds. Aim: The aim of this review is to provide an updated understanding of complex wound management through nursing intervention protocols, exploring methods for effective care, highlighting the importance of a team-based approach, and presenting new therapeutic strategies. Methods: The review adopts a comprehensive approach, discussing the anatomy and physiology of wound healing, contraindications for various therapies, and the roles of different healthcare professionals in wound care. A detailed analysis of key elements in wound assessment, such as infection, moisture balance, and tissue type, is provided. Results: The review highlights the crucial role of personalized, evidence-based treatment strategies in complex wound management. Key interventions include debridement techniques, the use of appropriate dressings, and infection control measures. It also emphasizes the importance of collaborative care among specialists, such as vascular surgeons, dietitians, and pain management teams, to optimize healing. Conclusion: Effective management of complex wounds requires a multidisciplinary approach, considering both physiological and psychological aspects of patient care. By tailoring treatment to individual needs and focusing on advanced therapeutic options, it is possible to improve healing outcomes and reduce the burden of complex wound care on both patients and healthcare systems.